Prevalence of online sexual harassment and online bullying: a nationwide survey among high school students in Denmark - Maj Britt Dahl Nielsen; Veronica Pisinger; Amalie Oxholm Kusier; Janne Tolstrup (Frontiers Media S.A., 2024)
BackgroundUsing data from a nationwide survey among high school students in Denmark, the aim of the current study is to measure the prevalence of online bullying and online sexual harassment and assess gender and age differences in exposure.MethodsWe used data from the Danish National Youth Study 2019, which is a nationwide web survey among high school students, including general, commercial, preparatory and technical high schools. Data were collected from January to April 2019 through a self-administered questionnaire in the classroom. A total of 29,086 students participated (response rate: 66%). The survey included questions about online sexual harassment (victimization and perpetration) and online bullying.ResultsApproximately 11% of students reported receiving sexually offensive inquiries online, and about 10% received a sexual image/video of others without the subjects' consent. Additionally, 4% experienced that other people shared a sexual image/video of them without their consent within the last 12 months. The most common type of online bullying was feeling ignored by others online (25%), followed by someone spreading rumors or writing nasty things about them (13%), and receiving threats/unpleasant messages (12%). Gender results were mixed.